Um olhar da Gestalt-terapia para o luto da criança: uma revisão integrativa de literatura - Camps, Patricia Barrachina (2022)
The purpose of this investigation was to broaden the current knowledge on the grieving process of children from the Gestalt therapy perspective, a dialogical approach that draws on the phenomenological-existential method to understand human phenomena. The Gestalt approach sees the human being as a continuous process of becoming—one of creative adjustments and organismic self-regulation—viewing the grieving process as an experience that breaks with previous life experience, requiring creative adjustments to accommodate the new reality emerging from the loss. An integrative literature review was conducted to identify publications addressing the grieving process in children from the theoretical and epistemological perspectives of Gestalt therapy. The inclusion criteria were studies in English or Portuguese, published during 2016-2021, and with full texts available online. “Grief” or “mourning” or “bereavement” and child* and “Gestalt therapy” (and, in Portuguese, “luto da criança” or “luto infantil” or “luto na infância” and “Gestalt-terapia”) were the descriptors employed in searches of the PubMed, Bireme-BVS (Lilacs, IBECS, MedLine, SciELO), CAPES Periodicals Portal, and Google Scholar databases, selected for their extensive content on scientific studies in this area of investigation. There is a dearth of studies on children’s grief using the Gestalt approach. Promoting research in this area can help expand the current knowledge base on the grieving process, as well as elucidate the potential for clinical interventions involving Gestalt therapy